Administrative agreements in brazilian IFES: Concept, state of the art and challenges (REMUNOM, 2024)
This Systematic Literature Review aimed to present the state of the art regarding the application of the device of administrative agreements in the Brazilian Federal Institutions of Higher Education, presenting information on conceptual aspects and the systematization of the obstacles encountered in the area. The Parsifal tool was used to support the execution of this RSL. After searching the chosen databases, established on the research protocol, 235 studies were found, including articles, dissertations and theses. After analyzing the title, abstract and keywords, applying the inclusion criteria, 225 works remained for full reading, which in the end resulted in 11 documents selected for the study. The results show that the scope of the publications is linked to agreements that include funding, instead, has been little studied about similar instruments with objects that are dedicated to technical-scientific cooperation. In addition, there was difficulty with excess, inadequacy and even non-compliance with the regulations that permeate the subject, as well as divergence in the interpretation of the standards between the IFES and the control bodies, in addition to the lack of uniformity in the processes. The findings of this research are relevant for formulators of public management policies of institutional partnerships to level the execution of the agreements, aligning the relationship between the IFES and other public or private entities, and mainly the relationship between these and their Supporting Foundations.